2023
DOI: 10.1177/10105395231158455
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Among Smartphone Use, Physical Activity, and Quality of Life in Chinese College Students

Abstract: This study aimed to investigate the correlations between smartphone use, physical activity, and quality of life (QOL) among Chinese college students. We enrolled 6323 students who were chosen from three Chinese universities. All participants completed the World Health Organization QOL Scale-Brief, Smartphone Addiction Index, and Physical Activity Questionnaire-Short Form. Smartphone addiction was negatively related to QOL (β = −1.375, 95% CI [–1.442, –1.306]), whereas physical activity was positively related t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…However, the prevalence of PMDs in our cohort aligns with findings from other population-based studies. 3,4 Third, although our study has adjusted for several known confounders, there remains the potential for residual confounding due to uncollected factors (e.g., physical activities) 68,69 and possible misclassification of confounders, such as the use of self-reported weight and height for BMI calculation. 70 Fourth, the participation rate was fairly good in the School of Medicine, while the lower rate in other schools is due to the ongoing data collection.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…However, the prevalence of PMDs in our cohort aligns with findings from other population-based studies. 3,4 Third, although our study has adjusted for several known confounders, there remains the potential for residual confounding due to uncollected factors (e.g., physical activities) 68,69 and possible misclassification of confounders, such as the use of self-reported weight and height for BMI calculation. 70 Fourth, the participation rate was fairly good in the School of Medicine, while the lower rate in other schools is due to the ongoing data collection.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…PMS can lead to significant distress and a decline in functional capacity. [1][2][3][4][5] Previous studies have indicated a relatively high frequency of PMS. Worldwide, it has been reported that approximately 47.8% of reproductive-age women are affected by PMS, with 5%-8% experiencing moderate to severe symptoms that are related to functional impairment.…”
Section: Introductionmentioning
confidence: 99%
“…Common manifestations of PMS include alterations in appetite, irritability, depression, anxiety, difficulty concentrating, headaches, weight gain, constipation, fatigue, abdominal and lower back pain, breast swelling and tenderness, as well as mood swings. PMS can lead to significant distress and a decline in functional capacity 1–5 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of them started their sports activities in the prepubertal and pubertal period, even before their first menstruation, before their puberty [1][2][3][4][5]. The intensity of physical and psycho-emotional stress increases significantly among female students at a physical education university, who specialize in a particular sport, then among their peers who are not so actively involved in physical education and sports [3][4][5][6][7][8][9]. The intensity of studying at the university, combining studies and sports, individual nutritional characteristics of girls, the presence or absence of a few bad habits, the formation, maintenance and level of their reproductive health is a very relevant topic for studying medical, biological and psychological processes occurring in the body.…”
Section: Introductionmentioning
confidence: 99%